Impacted inter-arytenoid chicken bone - Munjal, Manish; Gupta, Shikha; Singh, Tanvir; Rishi, Porshia; Sidhu, Harjnder; Munjal, Shubham; Binepal, Sivjot (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The anebriated individual with sluggish reflexes is likely to aspirate inadverently fluids, semisolids and solids alike. Fish and chicken preparations with their sharp skeletal bones may lacerate or get entangled in the mucosa of the upper aerodigestive tract. The tonsillar fauces, pyriform fossae, post cricoid region, supraglottis, glottis, subglottis, trachea, carina and either bronchi are the common sites of impaction of sharp-edged foreign bodies. We herein present a case involving a 40-year-old patient who had aspirated a laryngotracheal foreign body (chicken bone) 3 days prior to hospital admission, which was removed by tracheostomy and suspension microlaryngoscopy.